Q/F: The Texts of King Lear. (15th March 2021) - Salkeld, Duncan
Abstract: This article argues that dictation in the printing house may account for many of the variants between the 1608 Quarto and the 1623 Folio texts of King Lear . It further argues that the ground-work for this view was established by a series of prior critical studies—including those by Chambers, Greg, Duthie, Walker, and Stone—which shared a belief that the quarto was a reported text. It also proposes that a manuscript very much like F, but without its theatrical cuts, lies behind the Quarto. A long-standing assumption that the Folio version is somehow derived from the Quarto is shown to be unsafe. The implications of this argument are that Shakespeare did not revise King Lear, and that relatively few of the variants in the Quarto can be authorial.